In-situ X-ray radiography of twinned crystal growth of primary Al13Fe4. (15th July 2020) - Feng, S.; Cui, Y.; Liotti, E.; Lui, A.; Gourlay, C.M.; Grant, P.S.
Graphical abstract: Abstract: The faceted growth of primary Al13 Fe4 intermetallic compounds was studied using in-situ X-ray radiography in a solidifying Al-3Fe alloy. Microscopic twins were frequently observed in the growing intermetallics and were confirmed by post-solidification electron backscatter diffraction. A twin plane re-entrant growth mechanism was suggested, where repeated formation of re-entrant corners facilitated crystal growth along a preferential direction, forming elongated plates. In contrast, for intermetallics where this preferential growth was constrained by surrounding crystals, formation of layered twins perpendicular to the preferential direction was promoted and led to lower aspect ratios, known to be less deleterious to tensile properties.